Preparation method of green mixed cellulose detection film facilitating identification of light color bacterial strains

CN122665491BActive Publication Date: 2026-10-23JIANG SU AO DONG GAO XIN CAI LIAO KE JI YOU XIAN GONG SI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611131809.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

[0004]为解决上述技术问题,提供一种便于浅色菌种辨识的绿色混合纤维素检测膜制备方法,本技术方案解决了上述检测功能单一,难以满足精细化、智能化的微生物筛查需求的问题

Benefits of technology

本发明采用醋酸纤维素与硝酸纤维素3:1~5:1比例复配的混合纤维素基材,结合专属成膜工艺,大幅提升了滤膜综合使用性能。两种纤维素组分优势互补,既保留了醋酸纤维素良好的成膜均匀性、柔韧性与生物相容性,避免膜体脆裂破损,又兼具硝酸纤维素优异的微孔结构与微生物截留能力,保障检测过程中菌种有效截留、正常附着生长,不会抑制微生物代谢活性,适配各类浅色菌种的培养与检测需求,检测可靠性更高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122665491B_ABST
    Figure CN122665491B_ABST
Patent Text Reader

Abstract

The application discloses a green mixed cellulose detection film preparation method convenient for light color strain identification, relates to the technical field of microbial detection film materials, and specifically comprises the following steps: S1, mixed cellulose composed of cellulose acetate and nitrocellulose in a ratio of 3:1 to 5:1 is dissolved in a cosolvent, stirring and dissolving are carried out at 40-50 DEG C, chlorophyll microcapsules, pH responsive indicator microcapsules and film forming additives are added after cooling to below 35 DEG C, and low-speed stirring is carried out to remove bubbles; the chlorophyll microcapsules are embedded with natural chlorophyll by using gelatin-arabic gum wall materials, and the addition amount is 0.3%-1.0% of the mass of the mixed cellulose. The whole preparation process is simple, the conditions are mild, controllability is strong, and the process is suitable for large-scale industrial production; the highest reaction temperature in the whole process is not higher than 50 DEG C, the process conditions of low-temperature stirring, normal-temperature solidification and low-temperature drying are mild, the microcapsule structure and activity are not damaged, and the functional components are stable and effective.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microbial detection membrane technology, specifically to a method for preparing a green mixed cellulose detection membrane that facilitates the identification of light-colored bacterial species. Background Technology

[0002] Microbiological detection is a core testing item in fields such as food hygiene, water quality monitoring, biomedicine, and environmental testing. Membrane filtration methods, due to their advantages such as ease of operation, good enrichment effect, direct colony counting, and low testing cost, have become the mainstream technique for quantitative microbial detection and are widely used in the isolation, cultivation, and detection of various bacterial species. Mixed cellulose membranes are currently the most widely used membrane materials in the field of microbial detection. Among them, mixed cellulose membranes, which combine cellulose acetate and cellulose nitrate, possess excellent film-forming properties, porous permeability, biocompatibility, and chemical stability, meeting the basic requirements for microbial retention and cultivation, and are core consumables for standardized microbial testing.

[0003] Currently, most commercially available mixed cellulose detection membranes have white or milky-white transparent substrates. These present significant identification limitations when detecting light-colored, semi-transparent bacteria such as Staphylococcus aureus, yeast, and lactic acid bacteria. The color difference between light-colored bacterial colonies and the blank filter substrate is minimal, resulting in blurred colony edges and low visibility. This makes it difficult for testing personnel to quickly distinguish between the blank membrane and growing colonies, easily leading to missed detections, misjudgments, and large deviations in colony counts, significantly reducing the accuracy and efficiency of microbial detection. Furthermore, traditional detection membranes lack pH-responsive color development, failing to provide real-time feedback on bacterial growth status based on acidic or alkaline substances produced during bacterial metabolism. They rely solely on visual observation of colony morphology, offering limited detection capabilities and failing to meet the demands of refined and intelligent microbial screening. Conventional colorimetric membranes often have a uniform color structure with consistent color throughout, resulting in poor light transmittance. This not only obscures tiny light-colored colonies but also fails to adapt to the colorimetric identification requirements of bacteria at different growth stages, still failing to fundamentally address the technical pain point of low accuracy in identifying light-colored bacteria. In response, we propose a method for preparing a green mixed cellulose detection membrane that facilitates the identification of light-colored bacterial species. Summary of the Invention

[0004] To address the aforementioned technical problems, a method for preparing a green mixed cellulose detection membrane that facilitates the identification of light-colored bacterial species is provided. This technical solution solves the problem that the detection function is limited and cannot meet the needs of refined and intelligent microbial screening.

[0005] To achieve the above objectives, the technical solution adopted by this invention is as follows: a method for preparing a green mixed cellulose detection membrane that facilitates the identification of light-colored bacterial strains, the specific steps of which are: S1. A mixture of cellulose acetate and cellulose nitrate in a ratio of 3:1 to 5:1 is dissolved in a co-solvent and stirred at 40-50°C until dissolved. After cooling to below 35°C, chlorophyll microcapsules, pH-responsive indicator microcapsules, and film-forming aids are added, followed by low-speed stirring to remove bubbles. The chlorophyll microcapsules encapsulate natural chlorophyll using a gelatin-gum arabic wall material, with an addition amount of 0.3% to 1.0% of the mass of the mixed cellulose. The indicator microcapsules encapsulate bromothymol blue within a chitosan-sodium alginate semi-permeable membrane, with an addition amount of 0.1% to 0.4%. S2. The casting solution is coated onto the substrate with a doctor blade to a thickness of 80-120 μm and pre-evaporated for 2-5 min. The concentration gradient formed by the preferential evaporation of the solvent on the upper surface drives the microcapsules to migrate and accumulate on the upper surface, forming a gradient color structure with darker upper surface and lighter lower surface. S3. Immerse the membrane layer in a deionized water coagulation bath for 10-20 minutes to solidify it completely, forming a green porous mixed cellulose-based membrane. S4. Peel the cured base membrane from the substrate and soak it in deionized water 3-5 times, 10 minutes each time, to remove residual co-solvents, uncured raw materials and free pigments on the membrane surface; place the cleaned membrane in a low temperature constant temperature environment of 30-40℃ to dry it, and finally prepare a green mixed cellulose detection membrane that is easy to identify light-colored bacteria.

[0006] Preferably, the chlorophyll microcapsules described in S1 are prepared by a complex coagulation method. Natural chlorophyll is dispersed in a gelatin aqueous solution to form an inner aqueous phase, and gum arabic is dissolved in deionized water to form an outer aqueous phase. The pH of the system is adjusted to 4.0-4.5, and the inner aqueous phase is added to the outer aqueous phase at 40-50°C for emulsification. Then, the temperature is lowered to below 10°C to allow the gelatin-gum arabic complex coagulation to encapsulate the chlorophyll and form a wall material. After curing, washing, and drying, chlorophyll microcapsules are obtained.

[0007] Preferably, the indicator microcapsules described in S1 are prepared by electrostatic self-assembly. Bromothymol blue is dissolved in a pH 7.0 phosphate buffer solution as the core material droplet. Chitosan acetate solution is used as the first wall material layer, and sodium alginate aqueous solution is used as the second wall material layer. Chitosan layer and sodium alginate layer are alternately deposited on the surface of the core material droplet to form a semi-permeable membrane wall material. After washing and drying, the indicator microcapsules are obtained.

[0008] Preferably, the chlorophyll microcapsules in S1 have a particle size of 1 to 10 μm, and the indicator microcapsules have a particle size of 0.5 to 5 μm.

[0009] Preferably, the co-solvent in S1 is a mixture of acetone and ethanol in a volume ratio of 1:1 to 3:1; the stirring speed is 100 to 300 rpm, and the degassing time is 20 to 40 min.

[0010] Preferably, in the gradient color development structure described in S2, the ratio of the concentration of microcapsules on the upper surface of the membrane to the concentration of microcapsules on the lower surface is ≥2:1.

[0011] Preferably, in step S4, the upper surface of the detection membrane is dark green to provide a high-contrast detection background for colonies, while the lower surface is light green to ensure the normal penetration and diffusion of nutrients in the culture medium. When the metabolic acid production of colonies on the membrane surface causes the local pH to drop below 6.0, the upper surface indicates that the bromothymol blue inside the microcapsule changes from green to yellow, causing the green background around the colonies to locally change to yellow-green, forming a dual identification signal of background color change and colony body color.

[0012] Preferably, the drying time in S4 is 2 to 4 hours; the thickness of the resulting detection film is 60 to 100 μm, and the green color difference ΔE between the upper and lower surfaces is ≥15.

[0013] Preferably, the substrate in S2 is a clean and flat glass plate or stainless steel plate.

[0014] Preferably, the pre-evaporation environment in S2 is room temperature with a relative humidity of 40% to 60%.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes a mixed cellulose substrate composed of cellulose acetate and cellulose nitrate in a 3:1 to 5:1 ratio, combined with a proprietary film-forming process, significantly improving the overall performance of the filter membrane. The two cellulose components complement each other, retaining the excellent film-forming uniformity, flexibility, and biocompatibility of cellulose acetate to prevent membrane brittleness and breakage, while also possessing the superior microporous structure and microbial retention capacity of cellulose nitrate. This ensures effective retention and normal attachment and growth of microorganisms during detection, without inhibiting microbial metabolic activity, making it suitable for the cultivation and detection needs of various light-colored microorganisms, resulting in higher detection reliability.

[0016] This invention introduces a dual-color development system of chlorophyll microcapsules and pH-responsive indicator microcapsules, achieving the dual functions of substrate-supported color development and dynamic monitoring of bacterial growth, fundamentally solving the problem of identifying light-colored bacterial species. Specifically, the natural chlorophyll microcapsules embedded in the gelatin-gum arabic wall material enable the membrane to form a stable green substrate, creating a significant color contrast with light-colored, semi-transparent microbial colonies, greatly improving colony identification and effectively avoiding the problems of missed detection, misjudgment, and large counting errors caused by insufficient color difference in traditional white membranes.

[0017] The overall preparation process of this invention is simple, mild, and highly controllable, making it suitable for large-scale industrial production. The maximum reaction temperature throughout the process does not exceed 50°C, and the process conditions of low-temperature stirring, room-temperature curing, and low-temperature drying are mild and will not damage the microcapsule structure and activity, ensuring the stable efficacy of the functional components. At the same time, the process steps are simple, requiring no complex modification, post-dyeing, or finishing processes. It is easy to operate, has high production efficiency, and low preparation cost, and can be widely used in multiple fields such as food testing, water quality monitoring, environmental microbial screening, and biomedical testing. Attached Figure Description

[0018] Figure 1 This is a flowchart of the steps of the present invention. Detailed Implementation

[0019] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.

[0020] Example 1: Chlorophyll microcapsule encapsulation + gradient color development + pH-responsive dual-identification detection membrane Preparation of chlorophyll microcapsules 5g of natural chlorophyll (extracted from spinach leaves, purity ≥85%) was dispersed in 50mL of a 3% (w / v) gelatin aqueous solution and emulsified at 8000rpm for 5min to form the inner aqueous phase. 50mL of a 3% (w / v) gum arabic aqueous solution was placed in a reactor as the outer aqueous phase, and the temperature was raised to 45℃, adjusting the pH to 4.2. Under mechanical stirring at 600rpm, the inner aqueous phase was slowly added to the outer aqueous phase at a rate of 2mL / min, and emulsification was carried out for 15min. Subsequently, the system temperature was lowered to 8℃ at a cooling rate of 1℃ / min, and stirring was maintained for 30min. The gelatin-gum arabic underwent re-aggregation near the isoelectric point, encapsulating the chlorophyll to form microcapsule wall material. 0.5mL of glutaraldehyde solution (25%) was added for cross-linking and curing for 1h, followed by washing three times with deionized water and vacuum freeze-drying for 24h to obtain chlorophyll microcapsules. The average particle size of the microcapsules was determined to be 5.2 μm by a laser particle size analyzer, with a particle size distribution range of 1–10 μm.

[0021] The natural chlorophyll is extracted from spinach leaves, and the specific steps for achieving a purity of ≥85% are as follows: Raw material pretreatment: Select fresh, disease-free spinach leaves, remove the main vein and stem, wash with deionized water, absorb the water with filter paper, and cut the leaves into small pieces; weigh 100g of chopped leaves, add 2g of quartz sand and 1.5g of calcium carbonate, and grind them thoroughly in the dark into a homogenous paste. Solvent extraction: Add acetone-ethanol mixed extraction solution (volume ratio 2:1) at a material-to-liquid ratio of 1:8 (g:mL), and extract in the dark for 30 min; filter with gauze to collect the filtrate, repeat the extraction of the residue once, and combine all the filtrates; Concentration and extraction: Concentrate the filtrate under reduced pressure at 35℃ to 1 / 4 of the original volume, add an equal volume of petroleum ether for extraction, and control the water content of the system to 12%-16%; after standing and separating the layers, collect the upper layer of chlorophyll to enrich the petroleum ether organic phase, and discard the lower layer of aqueous phase impurities. Dehydration and purification: The organic phase was washed twice with a 5% sodium chloride aqueous solution to remove water-soluble impurities; anhydrous sodium sulfate was added for dehydration for 30 minutes, and the solution was filtered to obtain crude chlorophyll purified solution; Column chromatography purification: 100-200 mesh neutral alumina column chromatography was used, and the sample was loaded after the column was equilibrated with petroleum ether; elution was performed with petroleum ether-ethyl acetate (9:1 v / v), and the characteristic absorption peaks at 645 nm and 663 nm were monitored by ultraviolet spectrophotometer. The high-purity chlorophyll elution fractions were combined. The chlorophyll elution recovery rate in the column chromatography section was 92.3% (before optimization, the recovery rate of elution with a single 9:1 petroleum ether-ethyl acetate ratio was only 37.6%, and the recovery rate increased by more than 54 percentage points after optimization). Overall extraction recovery rate (from spinach raw material to finished chlorophyll powder): 1.12%; The final purity of the finished product was 86.7%, consistent with the original process. The increased elution intensity did not cause a decrease in product purity. Gradient elution not only solved the problems of excessive adsorption and incomplete elution of neutral alumina, but also accurately removed impurities and pigments through the low polarity eluent in the early stage, achieving a balance between recovery rate and product purity. Drying and purity testing: The eluent was concentrated under reduced pressure at 30℃, dried under vacuum at 25℃ to constant weight, and ground to obtain dark green chlorophyll powder; the purity of chlorophyll was 86.7% by Arnon method, which meets the requirement of ≥85% for use. It was sealed and stored in the dark for later use.

[0022] In this process, 5g of natural chlorophyll (extracted from spinach leaves, purity ≥85%) was dispersed in 50mL of a 3% (w / v) gelatin aqueous solution and emulsified at 8000rpm for 5min to form an internal aqueous phase. During this process, chlorophyll degradation was effectively prevented through a triple-pronged approach: low-temperature control, light-protection, and system aqueous phase protection. The specific steps are as follows: The emulsification system is an aqueous environment, where gelatin molecules form a preliminary hydration protective layer on the surface of chlorophyll particles, reducing the direct damage of strong shear forces to the chlorophyll molecular structure. The instantaneous heat generated by high-speed emulsification can be controlled within a low temperature range of 25℃ to 30℃ using a water bath to avoid local overheating that could lead to chlorophyll demagnesia and oxidative degradation. The entire process is carried out in the dark to prevent light-induced photo-oxidative decomposition and maintain the stability of chlorophyll structure to the greatest extent.

[0023] Detection by UV-Vis spectrophotometry showed no significant changes in the position and intensity of chlorophyll characteristic absorption peaks before and after emulsification. The chlorophyll retention rate during the emulsification process was 92%-96%, and the structure did not undergo significant degradation. It can be stably used for subsequent complex coagulation and embedding.

[0024] Preparation of pH-responsive indicator microcapsules 0.5 g of bromothymol blue was dissolved in 50 mL of pH 7.0 phosphate buffer solution (0.01 mol / L) as the core material solution. A 0.5% (w / v) chitosan acetate solution (dissolved in 1% acetic acid) was prepared as the first wall material layer solution, and a 0.5% (w / v) sodium alginate aqueous solution was prepared as the second wall material layer solution. An electrostatic self-assembly method was used: the core material solution was dropped into liquid paraffin containing 0.1% Span-80 and stirred at 1000 rpm to form a W / O emulsion; the chitosan acetate solution was added, and electrostatic adsorption was performed for 15 min to form the first wall material layer; then, sodium alginate aqueous solution was added, and electrostatic adsorption was performed for 15 min to form the second wall material layer; this process of alternating chitosan-sodium alginate deposition was repeated for 3 cycles, resulting in a total of 6 semi-permeable membrane wall materials. The liquid paraffin was removed by washing with n-hexane, followed by washing three times with deionized water, and vacuum drying for 12 h to obtain indicator microcapsules. The average particle size of the microcapsules was determined to be 2.8 μm by a laser particle size analyzer, with a particle size distribution range of 0.5–5 μm.

[0025] Casting solution preparation 4g of cellulose acetate (CA) and 1g of cellulose nitrate (CN) were compounded at a mass ratio of 4:1 to prepare a mixed cellulose. The mixed cellulose was added to 30mL of a mixed cosolvent prepared by acetone and ethanol at a volume ratio of 2:1, and stirred in a constant temperature water bath at 45℃ for 2h until completely dissolved. After cooling to 30℃, 0.035g of chlorophyll microcapsules (0.7% of the mass of the mixed cellulose), 0.015g of indicator microcapsules (0.3% of the mass of the mixed cellulose), and 0.3mL of glycerol film-forming aid were added sequentially. The mixture was stirred at low speed of 200rpm for 30min, and then allowed to stand for 30min to remove bubbles, resulting in a uniform and stable green modified casting solution.

[0026] Gradient casting molding Using a clean, flat glass plate as the casting substrate, the casting solution was uniformly coated onto the glass plate surface using a doctor blade coating method, with the coating thickness controlled at 100 μm. The coating was allowed to stand for 4 minutes at room temperature (25℃) and 50% relative humidity for pre-evaporation. During this pre-evaporation process, the solvent on the upper surface of the casting solution preferentially evaporated, forming a solvent concentration gradient from the upper to the lower surface. Since the density of chlorophyll microcapsules and indicator microcapsules is lower than that of the casting solution system, the convection migration effect driven by solvent evaporation caused the microcapsules to migrate directionally to the upper surface along the concentration gradient and accumulate, resulting in a significantly higher concentration of microcapsules on the upper surface than on the lower surface, forming a gradient color structure with darker upper surface and lighter lower surface. Cross-sectional scanning electron microscopy and elemental analysis showed that the ratio of microcapsule concentration on the upper surface to that on the lower surface was approximately 2.5:1.

[0027] Phase transformation and solidification film formation The pre-evaporated glass plate, along with the film layer, was rapidly immersed in a 25°C deionized water coagulation bath for phase inversion and curing, with a curing time of 15 minutes. The co-solvent in the casting solution exchanged solvent with the water in the coagulation bath, and the casting solution solidified to form a green porous mixed cellulose-based membrane.

[0028] In this process, the gelatin-gum arabic composite wall material of the chlorophyll microcapsules, after cross-linking and curing with glutaraldehyde, exhibits excellent water resistance, maintains structural integrity during phase inversion, and effectively blocks the effects of solvent exchange in the coagulation bath on the dissolution and degradation of the internal natural chlorophyll. The chitosan-sodium alginate semi-permeable membrane wall material of the indicator microcapsules possesses selective permeability: its pore size allows hydrogen ions to pass through. This allows small molecules to pass through while simultaneously blocking large molecular solvents such as acetone and ethanol in the coagulation bath from entering the microcapsule, thus protecting the bromothymol blue indicator from being washed away by the solvent.

[0029] The present invention characterizes the wall structure and tests the core material leakage rate of the prepared indicator microcapsules: Scanning electron microscopy (SEM) characterization was performed on the surface and cross-section of the microcapsules. The results showed that the cross-linked chitosan-sodium alginate formed a continuous, dense, and crack-free three-dimensional network semi-permeable membrane structure with uniform wall thickness and a complete structure free of structural defects. This dense network structure effectively blocks organic solvent molecules such as acetone and ethanol from entering the microcapsules, allowing only... , Small molecule ions can pass through, thereby achieving selective permeability.

[0030] Core material leakage rate determination in acetone system An equal amount of indicator microcapsules were dispersed in an acetone-water mixed solvent used in the casting solution and allowed to stand at room temperature for 2 hours to simulate the actual casting solution preparation environment. Subsequently, the microcapsules and solvent were separated by centrifugation, and the absorbance of bromothymol blue in the solvent phase was determined by ultraviolet-visible spectrophotometry. The core material leakage rate was then calculated.

[0031] Test results show that the bromothymol blue leakage rate is less than 2.3% in the presence of acetone, indicating that the microcapsule semipermeable membrane wall material has good density, which can effectively block acetone penetration, prevent the core material indicator from being washed away by the solvent, and ensure its stable retention in the membrane material.

[0032] In summary, the microcapsule wall material has a complete structure and high density, and can still maintain a good barrier effect in the acetone-containing casting solution system, ensuring that the core material does not dissolve or deactivate, thus providing support for the subsequent preparation and functional stability of green porous mixed cellulose-based membranes.

[0033] Post-processing refining The cured base film was peeled off from the glass plate and rinsed four times with deionized water for 10 minutes each time to remove residual co-solvents, uncured raw materials, and free components from the film surface. The cleaned film was then dried in a low-temperature constant temperature environment at 35°C for 3 hours, finally obtaining a green mixed cellulose detection membrane that is easy to identify light-colored bacterial species.

[0034] The thickness of the obtained test film was measured to be 82 μm. The upper surface was dark green and the lower surface was light green. The color difference between the upper and lower surfaces was ΔE=18.3.

[0035] Detection membrane function verification The prepared detection membrane was placed on a microbial detection platform: the upper surface facing upwards as the colony detection surface, and the lower surface facing downwards in contact with the culture medium. The dark green background on the upper surface provides strong contrast with the light / white colonies, facilitating counting and identification. The light green on the lower surface ensures normal penetration and diffusion of nutrients in the culture medium, without affecting normal microbial growth. When the metabolic acid production of the colonies causes the local pH on the membrane surface to drop below 6.0, the bromothymol blue inside the indicator microcapsules on the upper surface changes from green to yellow, and the green background around the colonies locally turns yellowish-green, forming a dual identification signal of "background color change + colony body color," significantly improving the reliability of identifying light-colored bacterial species.

[0036] Example 2: Low chlorophyll microcapsule dosage + short pre-evaporation time + rapid curing process Preparation of chlorophyll microcapsules The preparation method is the same as in Example 1, and the average particle size of the microcapsules is 4.5 μm.

[0037] Preparation of indicator microcapsules The preparation method was the same as in Example 1, and the average particle size of the microcapsules was 2.3 μm.

[0038] Casting solution preparation 3.75 g of cellulose acetate and 1.25 g of cellulose nitrate were mixed at a mass ratio of 3:1 to obtain a mixed cellulose. The mixed cellulose was added to 28 mL of a cosolvent prepared by mixing acetone and ethanol at a volume ratio of 1:1, and stirred in a constant temperature water bath at 40 °C for 2.5 h until completely dissolved. After cooling to 32 °C, 0.015 g of chlorophyll microcapsules (0.3% of the mass of the mixed cellulose), 0.005 g of indicator microcapsules (0.1% of the mass of the mixed cellulose), and 0.2 mL of glycerol film-forming aid were added sequentially. The mixture was stirred at a low speed of 150 rpm for 25 min, and then allowed to stand for 25 min to remove bubbles, thus obtaining the casting solution.

[0039] Gradient casting molding A clean, flat glass plate was used as the substrate for casting, and a coating thickness of 80 μm was applied using a doctor blade. The coating was pre-evaporated for 2 min at room temperature (23℃) and 55% relative humidity. Solvent evaporation drove the microcapsules to migrate to the upper surface, forming a gradient color structure. The ratio of microcapsule concentration on the upper surface to that on the lower surface was approximately 2.1:1.

[0040] Phase transformation and solidification film formation Immerse in a 25°C deionized water coagulation bath for 10 minutes to solidify and form the casting solution. The chlorophyll microcapsule wall material remains intact, indicating that the semi-permeable membrane of the microcapsules performs its selective permeation function.

[0041] Post-processing refining The base film was peeled off, and the film was rinsed three times with deionized water for 10 minutes each time, followed by drying at 35°C for 2 hours. The resulting test film had a thickness of 65 μm, and the green color difference between the upper and lower surfaces was ΔE = 15.6.

[0042] Example 3: High chlorophyll microcapsule addition + long pre-evaporation time + stainless steel substrate process Preparation of chlorophyll microcapsules The preparation method was the same as in Example 1, and the average particle size of the microcapsules was 6.8 μm.

[0043] Preparation of indicator microcapsules The preparation method is the same as in Example 1, and the average particle size of the microcapsules is 3.5 μm.

[0044] Casting solution preparation 4.17 g of cellulose acetate and 0.83 g of cellulose nitrate were mixed at a mass ratio of 5:1 to obtain a mixed cellulose. The mixed cellulose was added to a mixed cosolvent prepared by 32 mL of acetone and ethanol at a volume ratio of 3:1, and stirred in a 50 °C water bath for 1.5 h until completely dissolved. After cooling to 28 °C, 0.05 g of chlorophyll microcapsules (1.0% of the mass of the mixed cellulose), 0.02 g of indicator microcapsules (0.4% of the mass of the mixed cellulose), and 0.4 mL of glycerol film-forming aid were added sequentially. The mixture was stirred at 300 rpm for 40 min, and then allowed to stand for 40 min to remove bubbles, thus obtaining the casting solution.

[0045] Gradient casting molding A clean, flat stainless steel plate was used as the substrate for casting, and a coating thickness of 120 μm was applied using a doctor blade. Pre-evaporation was carried out for 5 minutes at room temperature (25℃) and 42% relative humidity. The longer pre-evaporation time allowed for more complete solvent evaporation, resulting in a more significant migration and enrichment of microcapsules to the upper surface, with a microcapsule concentration ratio on the upper surface to the lower surface of approximately 3.2:1.

[0046] Phase transformation and solidification film formation Immerse in a 25°C deionized water coagulation bath for 20 minutes to cure completely, ensuring the chlorophyll microcapsule wall material remains intact, indicating that the semi-permeable membrane of the microcapsules performs its selective permeation function.

[0047] Post-processing refining The base film was peeled off, and the sample was rinsed five times with deionized water for 10 minutes each time, followed by drying at 40°C for 4 hours. The resulting test film had a thickness of 98 μm, and the green color difference between the upper and lower surfaces was ΔE = 22.7.

[0048] Comparative Example 1: Direct addition of natural chlorophyll (without microencapsulation) The same CA:CN=4:1 mixed cellulose system and solubilizer ratio as in Example 1 were used. The difference was that chlorophyll microcapsules were not used in S1. Instead, 0.035g of natural chlorophyll powder (the same amount of pigment as in Example 1) and 0.015g of bromothymol blue powder (the same amount of indicator as in Example 1) were added directly. The remaining steps were the same as in Example 1, with a pre-evaporation of 1 min (no microcapsule migration required, following the conventional NIPS process).

[0049] Results: After film formation, the green color was uniformly distributed on both the upper and lower surfaces of the membrane, with a color difference ΔE=2.1. During the phase inversion process, natural chlorophyll was directly exposed to the coagulation bath, and approximately 62% of the chlorophyll was dissolved and lost through solvent exchange, resulting in a lighter-colored membrane after formation. Bromothymol blue was almost completely dissolved in the coagulation bath (dissolution rate >95%), and the membrane showed no pH-responsive color change function.

[0050] Comparative Example 2: Commercially available green mixed cellulose filter membrane A Sartorius CN138 green nitrocellulose filter membrane (47 mm in diameter, 0.45 μm in pore size) was used as a control. This filter membrane is a commercially available product, using a uniform coloring process, resulting in a consistent color on both the upper and lower surfaces of the membrane.

[0051] Results: The color difference ΔE between the upper and lower surfaces of the membrane was 1.8, indicating no gradient color development structure. Under the same microbial detection conditions, light-colored colonies (white / nearly transparent) were identifiable against a green background. However, when colonies were small (diameter <1 mm) or the color difference between the colonies and the background was small, visual identification was difficult, resulting in a high misidentification rate. The membrane lacked pH-responsive color change capability and relied solely on static color comparison.

[0052] Comparative Example 3: Direct addition of sodium copper chlorophyllin (a common stabilization method in existing technologies) The same CA:CN=4:1 mixed cellulose system and solubilizer ratio as in Example 1 were used. The difference was that in S1, 0.035g of sodium copper chlorophyllin salt was used instead of chlorophyllin microcapsules (equal amount of pigment), and 0.015g of bromothymol blue powder was used instead of indicator microcapsules. The casting solution was added directly, and the remaining steps were the same as in Example 1.

[0053] Results: The dissolution rate of sodium copper chlorophyll during phase inversion was approximately 28% (lower than that of natural chlorophyll, but still a significant loss). The resulting membrane was blue-green, showing a color deviation from the grass-green of pure natural chlorophyll. Bromothymol blue dissolution rate was >90%, and the membrane showed no pH response. The coloring was uniform across both surfaces, with ΔE = 3.4.

[0054] Performance testing and data comparison Test conditions Bacterial strains: Escherichia coli (ATCC 25922, white colonies), Candida albicans (ATCC 10231, nearly transparent colonies); Culture medium: Nutrient agar plates (pH 7.2). Culture conditions: Escherichia coli was cultured at 37°C for 24 hours, and Candida albicans was cultured at 28°C for 48 hours; Pigment retention rate determination: UV-Vis spectrophotometer, with the absorbance measured immediately after film formation as 100%, and the retention rate calculated again after culture; Nutrient permeation rate: The membrane was placed in a Franz diffusion cell with glucose solution (0.1 mol / L) in the upper chamber and deionized water in the lower chamber. The amount of glucose permeated was measured within 60 min. Accuracy of light-colored colony identification: Five researchers counted the colonies independently, and the results were compared with those from fluorescence microscopy to calculate the accuracy.

[0055] The table below is a comparison of overall performance. From the table above, we can see that: Microencapsulation enhances pigment stability In Examples 1-3, the chlorophyll retention rate exceeded 92% after phase inversion and remained above 86% after 48 hours of incubation. In Comparative Example 1, natural chlorophyll was directly added, resulting in a retention rate of only 38.1% after phase inversion, which dropped to 12.4% after 48 hours, with the membrane essentially fading and failing. Comparative Example 3 used sodium copper chlorophyll, which, although chemically more stable than natural chlorophyll, lacked wall material protection due to its direct addition method, resulting in a retention rate of only 63.7% after 48 hours. Microencapsulation increased the chlorophyll retention rate by approximately 3.5 times compared to the direct addition of natural chlorophyll and by approximately 1.4 times compared to the direct addition of sodium copper chlorophyll.

[0056] Synergistic optimization of detection sensitivity and nutrient penetration by gradient color development structure In Examples 1-3, the color difference ΔE between the upper and lower surfaces ranged from 15.6 to 22.7. The dark green upper surface provided a high-contrast detection background, while the light green lower surface reduced resistance to nutrient penetration. Comparative Examples 1-3 all had uniformly colored structures, with ΔE ranging from only 1.8 to 3.4, indicating insufficient contrast on the upper surface. Regarding nutrient penetration, the glucose penetration amount at 60 minutes in Example 1 (4.82 mg / cm²) was close to that of the uniformly colored Comparative Examples 1 (4.95 mg / cm²) and 2 (5.08 mg / cm²), demonstrating that the gradient structure did not significantly reduce nutrient penetration performance under low microcapsule concentration conditions on the lower surface, achieving a balance between detection sensitivity and nutrient penetration efficiency.

[0057] Enhanced recognition of light-colored colonies by pH-responsive dual-signal identification Examples 1-3 feature pH-responsive color-changing functionality. When the colony produces acid, causing the local pH to drop below 6.0, the background changes from green to yellowish-green, forming a dual identification signal of "background color change + colony body color." Example 1 achieved a 95.6% accuracy rate in identifying Candida albicans (nearly transparent colonies), with the pH-responsive area further improving to 99.1%. Comparative Example 2 (commercially available green film) had an accuracy rate of only 71.4% in identifying Candida albicans, lacking a dynamic color-changing signal. The visual identification of near-transparent colonies relied on static comparison, resulting in a high misjudgment rate. The pH-responsive function improved the accuracy rate of identifying near-transparent colonies by approximately 24 percentage points.

[0058] Comparative Example 1, lacking both microencapsulation, gradient structure, and pH-responsive functionality, achieved an accuracy of only 62.8% in identifying Candida albicans. Example 1, integrating these three innovative approaches, improved this accuracy to 95.6% (static identification) and 99.1% (pH-responsive region), representing an overall improvement of approximately 32–36 percentage points. The three approaches address the issues of "pigment stability—structural-functional differentiation—enhanced dynamic identification," exhibiting a significant synergistic effect: microencapsulation ensures the material basis for gradient distribution and pH-responsive functionality; the gradient structure optimizes the functional differentiation of the upper and lower surfaces; and the pH response superimposes a dynamic color-changing signal onto a stable green background, resulting in a technical effect where 1+1+1>3.

[0059] The accuracy of colony identification in the pH response zone of Examples 1-3 was consistently above 98%, with Example 3 showing the highest accuracy (99.4%). This indicates that the pH-responsive color-changing system based on chlorophyll microcapsules can provide clear and stable visual signals for colony identification, significantly reducing the probability of misjudgment. Compared with the non-pH-responsive system, the comparative examples do not have pH-responsive color-changing function, and cannot intuitively distinguish colony areas through color changes. Therefore, this identification cannot be carried out, which demonstrates the unique advantage of this invention in intelligent visual colony detection. This high accuracy can support rapid screening of pathogenic microorganisms in food, medical and other fields, reduce human interpretation errors, and improve detection efficiency and reliability.

[0060] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains, characterized in that, The specific steps are as follows: S1. A mixture of cellulose acetate and cellulose nitrate in a ratio of 3:1 to 5:1 is dissolved in a co-solvent and stirred at 40-50°C until dissolved. After cooling to below 35°C, chlorophyll microcapsules, pH-responsive indicator microcapsules, and film-forming aids are added, followed by low-speed stirring to remove bubbles. The chlorophyll microcapsules encapsulate natural chlorophyll using a gelatin-gum arabic wall material, with an addition amount of 0.3% to 1.0% of the mass of the mixed cellulose. The indicator microcapsules encapsulate bromothymol blue within a chitosan-sodium alginate semi-permeable membrane, with an addition amount of 0.1% to 0.4%. S2. The casting solution is coated onto the substrate with a doctor blade to a thickness of 80-120 μm and pre-evaporated for 2-5 min. The concentration gradient formed by the preferential evaporation of the solvent on the upper surface drives the microcapsules to migrate and accumulate on the upper surface, forming a gradient color structure with darker upper surface and lighter lower surface. S3. Immerse the membrane layer in a deionized water coagulation bath for 10-20 minutes to solidify it completely, forming a green porous mixed cellulose-based membrane. S4. Peel the cured base membrane from the substrate and soak it in deionized water 3 to 5 times, 10 minutes each time, to remove residual co-solvent, uncured raw materials and free pigments on the surface of the membrane. Place the cleaned membrane in a low temperature constant temperature environment of 30 to 40°C to dry it, and finally prepare a green mixed cellulose detection membrane that is easy to identify light-colored bacteria. The chlorophyll microcapsules described in S1 are prepared by a complex coagulation method. Natural chlorophyll is dispersed in a gelatin aqueous solution to form an inner aqueous phase, and gum arabic is dissolved in deionized water to form an outer aqueous phase. The pH of the system is adjusted to 4.0-4.5, and the inner aqueous phase is added to the outer aqueous phase at 40-50°C for emulsification. Then, the temperature is lowered to below 10°C to allow the gelatin-gum arabic complex coagulation to encapsulate the chlorophyll and form a wall material. After curing, washing, and drying, chlorophyll microcapsules are obtained.

2. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial species according to claim 1, characterized in that: The indicator microcapsules described in S1 are prepared by electrostatic self-assembly. Bromothymol blue is dissolved in a pH 7.0 phosphate buffer solution as the core material droplet. Chitosan acetate solution is used as the first wall material layer, and sodium alginate aqueous solution is used as the second wall material layer. Chitosan layer and sodium alginate layer are alternately deposited on the surface of the core material droplet to form a semi-permeable membrane wall material. After washing and drying, the indicator microcapsules are obtained.

3. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains according to claim 1, characterized in that: The chlorophyll microcapsules in S1 have a particle size of 1–10 μm, and the indicator microcapsules have a particle size of 0.5–5 μm.

4. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains according to claim 1, characterized in that: The co-solvent mentioned in S1 is a mixture of acetone and ethanol in a volume ratio of 1:1 to 3:1; the stirring speed is 100 to 300 rpm and the degassing time is 20 to 40 min.

5. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains according to claim 1, characterized in that: In the gradient colorimetric structure described in S2, the ratio of the concentration of microcapsules on the upper surface of the membrane to the concentration of microcapsules on the lower surface is ≥2:

1.

6. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains according to claim 1, characterized in that: The detection membrane described in S4 has a dark green upper surface to provide a high-contrast detection background for colonies, and a light green lower surface to ensure the normal penetration and diffusion of nutrients in the culture medium. When the colonies on the membrane surface produce acid through metabolism, causing the local pH to drop below 6.0, the bromothymol blue in the microcapsules on the upper surface changes from green to yellow, causing the green background around the colonies to locally turn yellow-green, forming a dual identification signal of background color change and colony body color.

7. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial species according to claim 1, characterized in that: The time for drying the cleaned membrane in a low-temperature constant temperature environment of 30-40℃ as described in S4 is 2-4 hours; the thickness of the resulting test membrane is 60-100μm, and the green color difference ΔE between the upper and lower surfaces is ≥15.

8. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial strains according to claim 1, characterized in that: The substrate described in S2 is a clean and flat glass plate or stainless steel plate.

9. The method for preparing a green mixed cellulose detection membrane for easy identification of light-colored bacterial species according to claim 1, characterized in that: The pre-volatile environment described in S2 is room temperature with a relative humidity of 40% to 60%.

Citation Information

Patent Citations

  • Method for preparing n-butyl alcohol in fermentation mode by hydrolyzing lignocellulose through mixed cellulose crude enzyme

    CN104004794A

  • Detection device and method for detecting analyte in liquid sample

    CN107621539A